HUBUNGAN PEMBERIAN REWARD DENGAN MINAT BELAJAR SISWA MTs DARUL ILMI - Rahmarani Akmal Hia (EDUCATE, 2025)
This study aims to determine the relationship between reward giving and learning interest in eighth grade students of MTs Darul Ilmi. Based on the observation results, it was found that during the learning process, the teacher had given rewards but not optimally. This study was conducted using quantitative research methods. Based on the data and hypotheses, the reward variable has a relationship with the learning interest variable. This can be seen that the proposed hypothesis is accepted, namely with the value of "r" product moment, namely 0.815. The data is assumed to be normally distributed and has a homogeneous variant so that based on the results of hypothesis testing related to the formulation of the problem using the PPM (Pearson Product Moment) correlation formula, the rxy price is 0.815 which is greater than r table 0.374, namely 0.53> 0.374, so it can be seen that the alternative hypothesis (Ha) in this study is accepted. This means that there is a relationship between rewards and students' learning interest, so it can be concluded that the theory stating that "Factors that can influence the emergence of learning interest in students, one of which is social factors where someone is interested in high achievement in order to get high social status and get recognition or appreciation from the environment he is in" is proven true.